The Evaluation for Accuracy of Non-Destructive Testing (NDT) in Ultrasonic Inspection on Mild Steel Material by Ultrasonic Testing Thickness Measurement (UTTM) - Nur Artisya Zulkipli; M Yusup, Eliza (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Ultrasonic testing (UT) refers to a group of non-destructive testing techniques that include sending ultrasonic waves through a substance or object. Ultrasonic testing is frequently utilized in industrial applications on metals, polymers, composites, and ceramics. UT is used for thickness measurement when ultrasound wave reflected back to the surface. This study is to analyze the thickness measurement of mild steel plate using three different measuring tools which are ruler, vernier caliper and ultrasonic testing. Also, the Ultrasonic Testing Thickness Measurement (UTTM) method is applied with couplant such as oil, water and grease to evaluate the thickness properties using single probe and twin probe. The ultrasonic waves will pass through the transmitter and receiver of mild steel plate for UTTM method. After constructing the experiment for 30 days exposing to environment, the result obtained from the study shows that UTTM method can be applied to 5 mm mild steel plate. Overall, the percentage difference of UTTM compared to Vernier Calliper is only 1 to 2%, while 10% compared to ruler. Thus, UTTM can be applied for thickness measurement especially for complicated or material that only require one side access.